Exercising a firm’s growth options: A portfolio approach - Andrés, Pablo de; Fuente, Gabriel de la; Velasco, Pilar (Journal of business research, 2021)
•The hedging potential of GO from prior explorative investments.•The portfolio of businesses as a basis of analysis for the decision to exercise GO.•A firm’s level of diversification deters GO exercise.•The average volatility of a firm’s current businesses discourages GO exercise.•Relatedness and rivalry in its core business trigger GO exercise. This paper investigates a firm’s decision to exercise its growth options within the current scope of business. We contend that the point at which a firm chooses whether or not to exercise such options depends on several strategic characteristics associated to its portfolio of businesses (i.e. level of diversification, average volatility of its current business, relatedness among them, and rivalry in its core business). Using a sample of U.S. companies from 1998 to 2013, we find evidence that a firm’s level of diversification and the volatility of its current business deter immediate growth option exercise. In contrast, relatedness and rivalry in its core business trigger growth options exercise. Our portfolio perspective differs from the bulk of the literature on real options, which evaluates each growth option exercise in isolation, and contributes to furthering knowledge on the drivers underlying a diversified firm's strategic investments.